A influência do gerente de conta no uso do internet banking pelo cliente alta renda no Brasil: um estudo de caso - Santos, Adriana Maria dos (2007)
The present study was held in a segment of individual clients with high earnings of a big retail bank in Brazil and was focused on the municipality of São Paulo. The investigation aimed to verify whether there has been any relation between the account manager profile, as to his or her technology and internet knowledge and ability, and the level of adoption of the Internet Banking by clients under his or her orientation. For this investigation it was adopted a qualitative approach which consisted of internal data analysis, interviews, and questionnaire sent to a group of account managers. The results (1) suggest that even in the high earnings segment there have been other variables as age and the credit of salary in current account that affect the level of use of Internet Banking by clients; and that the manager profiles differ in terms of level of involvement with new technologies, which includes the internet; and (2) signalize that account managers whose profile is more technologically advanced make use of the internet more naturally and present stronger power of convincement over clients under his or her orientation as to Internet Banking adoption.